The Influence of Tourism Awareness Work Culture on Community Satisfaction Visiting Aie Manih Beach, Padang, West Sumatra - Aldri Frinaldi; Afriva Khaidir (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The need for tourism at this time is something that is needed by various individuals, families and communities. One of the efforts to increase the satisfaction of visiting people is to build a tourism-aware work culture among the tourism apparatus and community in a tourist location. The formulation of the problem in this study are; Is there an influence of the tourism awareness work culture of the tourism apparatus and the tourist community on the satisfaction of the people visiting tourist sites in West Sumatra?. The research method is quantitative by distributing questionnaires to respondents who were selected by purposive and incidental sampling. Respondents related to the apparatus in the city of Padang as many as 39 people, the tourism community at tourist sites as many as 37 people, and the people visiting as many as 213 people. The results obtained in this study are the results of each independent variable, so it appears to have a significant influence on Y. The magnitude of the influence is; Simultaneously, the influence of the variables of the tourism conscious work culture of the apparatus and the tourist community on the satisfaction of the visiting community was 66.5% with a TCR result of 88.6% with a very good category at the Aie Manih Beach location; Simultaneously, the influence of the variables of the tourist community on the satisfaction of the visiting people is 64.6% with a very good TCR result of 91.6% and the satisfaction of the visiting community has a correlation of 36.0% with a TCR result of 84.2% with a very good result. Work culture on the satisfaction of visiting people has a significant value of 0.000 at the Aie Manih Beach location.